Rent control effects through the lens of empirical research: An almost complete review of the literature - Konstantin Kholodilin (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
Rent control is a highly debated social policy that has been omnipresent since World War I. Since the 2010s, it is experiencing a true renaissance, for many cities and countries facing chronic housing shortages are desperately looking for solution, directing their attention to controling housing rents and other restrictive policies. Is rent control useful or does it create more damage than utility? To answer this question, we need to identify the effects of rent control. This study reviews a large empirical literature looking at various aspects of rent controls. We conclude that rent controls are quite effective in terms of lowering housing rents or slowing their growth, but they also lead to a wide range of adverse effects affecting both landlords and tenants.
Keywords: K25; N90; R38; 330; rent control; housing policy; empirical literature review